The Correlation between Students' Habits in Watching English Movies with English Subtitles and Their Speaking Skills at SMAN 7 Manado - Nofry Frans; Marceliana, H Mansiarang; Vera Wahani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study employed a quantitative approach to explore the relationship between students' habits of watching English-language films with English subtitles and their proficiency in speaking English. The sample consisted of 100 tenth-grade students from SMAN 7 Manado during the first semester of the 2023/2024 academic year, drawn from classes A, C, and D. Data were analysed using descriptive statistics (Mean) and the Pearson Product-Moment Correlation Coefficient. The results indicated that the mean score for students' viewing habits was 2.61, reflecting a moderate frequency, while the mean score for speaking proficiency was 3.32, also indicating a moderate level. The correlation analysis yielded a p-value of 0.061 and a correlation coefficient of 0.188, suggesting a statistically insignificant but positive and weak relationship between the two variables. Although the correlation was not statistically significant, the findings imply that exposure to English films with subtitles may support the development of speaking skills. Therefore, the study provides a research-based implication that media-based learning strategies, specifically subtitled film viewing, can be integrated into curriculum design as a supplementary method to enhance students’ speaking proficiency, especially when tailored to their individual learning preferences and supported by structured pedagogical frameworks.